Стан NO-системи в тромбоцитах крові хворих на ідіопатичну легеневу гіпертензію та його зміни в умовах лікування блокатором кальцієвих каналів дилтіаземом - Амосова, К.М.; Коцюбура, А.В.; Задорін, Є.М.; Губський, Ю.І.; Конопльова, Л.Ф. (Видавничий дім "Академперіодика" НАН України, 2007)
A considerable decrease of constitutive NO-syntase activity (cNOS) in blood thrombocytes of patients with idiopathic pulmonary hypertension (IPH) is shown. This is the evidence of a decrease of NO synthesis with vaso-dilating properties and an increase of inducible NO-syntase activity (iNOS), that is accompanied by increase of the pool of nitrate-anions (NO–3) and promotes the activation of lipids peroxidation. Activity of Ca2+ — dependent cNOS in blood thrombocytes of patients with IPH increases, and the part of NO–2 of the stable metabolites pool increases under treatment with diltiazem. This is the evidence of the activation of NO pool production with vaso-dilating properties. Treatment with diltiazem doesn't influence the activity Ca2+ — independent iNOS and the NO–3 pool.